Classification of Semes of the Verb Word Group (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The given article expresses the attitude of the scientific views of such linguists as A. Gulomov, A. Hojiyev, H. Ne'matov, R. Rasulov, who separately studied the research of the verb word group in Uzbek linguistics. Since verb lexemes express a character or a state in action, the problem of different manifestation of graduonymic lines, observation of special gradation phenomena in verb categories and semantic groups was analyzed.